Evaluation of an electronic sensor-based agility test system for badminton players' development - Marrylin Yalin, J. E.; Haris, H.; Hasnan, M. M. I. M.; Saad, I. (IEEE Xplore, 2022)
Badminton requires quick movements, high-intensity repeated actions, and precise foot movements to maximize shot accuracy. This emphasizes the need for agility in badminton games. Numerous tests are used to assess agility. However, badminton lacked a specialized agility test based on the game's nature. This project aims to create a modified version of an agility test system specified for amateur badminton players that emphasizes footwork, change of direction speed (CODS), and reactive agility (RA). The ATmega328, Adjustable Infrared Sensor Switch, Force Sensitive Resistor, and RF communication module created Badminton Agility System (BAS). This combination allows players to control the test flow according to their abilities. This study presents a new technological approach to sensor system design for sports measurement, focusing on measuring parameters for assessing agility in amateur athletes. Second is the capability to perform precise and accurate semi-automatic measures in sync with the player's abilities. The system's functioning was tested using a replica court prototype and the actual prototype. The data tested for five participants showed that the mean total time for each direction was between four and five seconds, with a maximum of 25 seconds and a minimum of 15 seconds required to complete the test. This data indicates that the Badminton Agility System optimizes badminton agility testing. Due to the reactive agility factor, the reaction time to different targets revealed that amateur players need more time for forward movement than backward movement. The reaching time and return time have demonstrated significant variances, and the system could communicate between the control part without substantial changes. In addition, the total time spent at each position revealed the participant's areas for future improvement. The test results show that the system can perform the agility process reliably. All three components considered while constructing this test might well be studied in the future.